Pengembangan Potensi Sistem Informasi Digital Dalam Menjaga Kebertahanan Identitas Lokal Kampung Bersejarah Kayutangan (TEKAD : Teknik Mengabdi, 2025)
Kampoeng Heritage Kayutangan is a flagship thematic tourism village in Malang City, rich with distinctive colonial architecture and a collection of vintage objects of high historical value. However, increased tourism activity in the area poses a major challenge in preserving the historical and environmental values of the settlement. Threats to the authenticity of historic architecture and the integrity of local culture within Kampoeng Heritage Kayutangan are crucial issues that require special attention. Therefore, technology-based preservation efforts can be one of the important preservation methods. This method integrates aspects of preservation with tourism development. The purpose of this community service activity (PKM) is to identify, document, and digitally map the historical buildings of Kampoeng Heritage Kayutangan. Digital building data collection applies 360 camera technology and 3D modeling. This digital mapping can provide accurate data that can be used by the government and other stakeholders in designing preservation policies. This mapping can also improve the tourism information system that supports the sustainable management of this village. The results of this PKM are expected to be able to make a real contribution to the development of Kampoeng Heritage Kayutangan as a sustainable heritage tourism destination and strengthen collaboration between the local community and the government in preserving the culture of the area. Through this approach, it is hoped that this PKM activity can make a real contribution to the preservation and promotion of Kampoeng Heritage Kayutangan as a tourist destination that combines aspects of cultural preservation with tourism-based economic development.